Outcome of Minimally Invasive Spine Surgery for Degenerative Spine Disease in Tertiary Care Hospital - Jatoi, Asif Ali; Muhammad Bilal; Janjua, Faizan Ali; Jan, Abdullah; Qureshi, Muhammad Asad; Aslam, Ejaz (Indus Journal of Bioscience Research, 2025)
Background: Degenerative spine disease is a common cause of chronic pain and disability, often requiring surgical intervention when conservative measures fail. Minimally invasive spine surgery (MISS) has gained prominence as an alternative to open procedures, with the aim of reducing morbidity while achieving similar or superior outcomes. Objective: The purpose of this study was to evaluate the clinical and functional outcomes of MISS in patients with degenerative spinal disorders treated at a tertiary care hospital. Methods: A prospective observational study was conducted on 67 patients who underwent MISS between February 2024 and February 2025. Clinical data, operative parameters, complications, and follow-up outcomes were recorded. Pain and disability were measured using the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI), respectively. Statistical analysis was performed to compare pre- and postoperative scores, with p < 0.05 considered significant. Results: The mean age of the patients was 52.8 years, with a male-to-female ratio of 1.4:1. Lumbar disc herniation (43.3%) was the most common pathology, followed by spinal stenosis (37.3%) and spondylolisthesis (19.4%). The mean operative time was 112 minutes, and mean blood loss was 126 ml. Conversion to open surgery occurred in 3% of cases. Pain scores improved significantly from 7.2 to 2.1 (p < 0.001), and ODI decreased from 58.4% to 18.7% (p < 0.001) at six months. Neurological recovery was observed in 85.7% of patients with baseline deficits. Complication rates were low, with infections in 4.5% and reoperations in 3%. Conclusion: MISS is a safe and effective surgical option for degenerative spine disease, offering significant improvements in pain, disability, and neurological recovery, with low complication rates. The results support its role as a reliable alternative to open procedures in tertiary care practice.